THE CONNECTION BETWEEN PSYCHOLINGUISTICS AND LEXICOLOGY IN TEACHING ENGLISH LANGUAGE (International journal of artificial intelligence, 2024)
This article explores the intricate relationship between psycholinguistics and lexicology, focusing on their shared interest in the mental lexicon and vocabulary acquisition. While psycholinguistics studies the cognitive processes of language comprehension, production, and storage, lexicology provides theoretical frameworks for analyzing word structure, meaning, and relationships. Drawing on studies of word recognition, semantic networks, and morphological processing, this review highlights how psycholinguistic insights support lexicological theories and vice versa. Findings emphasize the mutual benefits of an interdisciplinary approach, with applications in language education, lexicography, and cognitive science.